Examination of Digital Literacy Levels of University Students - Halil İbrahim Kaya; Murat Korucuk (Dinamika Ilmu, 2022)
In this study, it was aimed to determine the digital literacy levels of university students. The study also aimed to examine the differentiation status of university students in terms of various variables of digital literacy levels. In addition, in the study, the digital literacy levels of university students were determined by gender, type of education (normal/secondary education), higher education level (associate / undergraduate/graduate), higher education program they are enrolled in, grade point average, class, average monthly income, social network with the most time spent. It is also aimed to examine the differentiation status in terms of the variables of average internet usage time during the day, the preferred tool for internet use, and the educational status of the parents. In this study, the survey model, which is one of the quantitative patterns, was used. The population of the study consisted of a total of 17,006 students, 11,500 undergraduate and 5,506 associate degree students, studying in 11 faculties, 4 colleges and 9 vocational colleges in the 2021-2022 academic year at a state university located in the Eastern Anatolia Region. The sample consisted of randomly selected 688 university students. The "Digital Literacy Scale" developed by Bayrakçı and Narmanlıoğlu in 2021 was used as a data collection tool. In the analysis process, nonparametric techniques were used since the data could not meet the assumptions of parametric techniques. As a result of the study, it was seen that the digital literacy levels of university students were low. In addition, it was concluded that there were statistically significant differences between university students' grade point averages, the social network they spend the most time on, the preferred tool in internet use, and the educational status of their parents and their digital literacy levels. Various suggestions were developed considering the results of the study.